Power and Politics in the Global Health Landscape: Beliefs, Competition and Negotiation Among Global Advocacy Coalitions in the Policy-Making Process - Lori McDougall (Kerman University of Medical Sciences, 2016)
Background Advocacy coalitions play an increasingly prominent role within the global health landscape, linking actors and institutions to attract political attention and resources. This paper examines how coalitions negotiate among themselves and exercise hidden forms of power to produce policy on the basis of their beliefs and strategic interests. Methods This paper examines the beliefs and behaviours of health advocacy coalitions using Sabatier's Advocacy Coalition Framework (ACF) as an informal theoretical lens. Coalitions are further explored in relation to the concept of transnational advocacy networks (Keck and Sikkink) and of productive power (Shiffman). The ACF focuses on explaining how policy change takes place when there is conflict concerning goals and technical approaches among different actors. This study uses participant observation methods, self-reported survey results and semistructured qualitative interviews to trace how a major policy project of the Millennium Development Goal (MDG) era, the Global Strategy for Women's and Children's Health, was constructed through negotiations among maternal, newborn, and child health (MNCH) and sexual and reproductive health and rights (SRHR) advocacy coalitions. Results The Global Strategy represented a new opportunity for high-level political attention. Despite differing policy beliefs, MNCH and SRHR actors collaborated to produce this strategy because of anticipated gains in political attention. While core beliefs did not shift fundamentally and collaboration was primarily a short-term tactical response to a time-bound opportunity, MNCH actors began to focus more on human rights perspectives and SRHR actors adopted greater use of quantifiable indicators and economic argumentation. This shift emphasises the inherent importance of SRHR to maternal and child health survival. Conclusion As opportunities arise, coalitions respond based on principles and policy beliefs, as well as to perceptions of advantage. Global health policy-making is an arena of contested interests, power and ideas, shaped by the interaction of coalitions. Although policy-making is often seen as a process that should be guided by evidence rather than interest-based politics, this study concludes that a participatory process of debate among different actorcoalitions is vital to progress and can lend greater legitimacy, accountability and transparency to the policy process.